Unraveling the intricate link between cell death and neuroinflammation using Drosophila as a model - Rai, Pooja; Bergmann, Andreas (Frontiers in Cell and Developmental Biology, 2024)
Protein aggregation is a common pathological occurrence in neurodegenerative diseases. This often leads to neuroinflammation, which exacerbates the aggregation and progression of diseases like Parkinson’s and Alzheimer’s. Here, we focus on immune responses and neurotoxicity in a Parkinson’s disease model in Drosophila. Mutations in the SNCA gene that encodes the alpha (α)-Synuclein protein have been linked to familial Parkinson’s disease, disrupting autophagy regulation in neuronal cells and promoting the formation of Lewy bodies, a hallmark of Parkinson’s pathology. This results in the loss of dopaminergic neurons, manifesting as movement disorders. α-Synuclein aggregation triggers innate immune responses by activating microglial cells, leading to phagocytic activity and the expression of neuroprotective antimicrobial peptides (AMPs). However, sustained AMP expression or chronic inflammation resulting from inadequate microglial phagocytosis can induce neuronal toxicity and apoptosis, leading to severe dopaminergic neuron loss. This review underscores the mechanistic connection between immune response pathways and α-Synuclein-mediated neurodegeneration using Drosophila models. Furthermore, we extensively explore factors influencing neuroinflammation and key immune signaling pathways implicated in neurodegenerative diseases, particularly Parkinson’s disease. Given the limited success of traditional treatments, recent research has focused on therapies targeting inflammatory signaling pathways. Some of these approaches have shown promising results in animal models and clinical trials. We provide an overview of current therapeutic strategies showing potential in treating neurodegenerative diseases, offering new avenues for future research and treatment development.